Plantar pressure changes in hindfoot relief devices of different designs - Mazur, Felix; Swoboda, Bernd; Carl, H. D.; Lutter, C.; Engelhardt, M.; Hoppe, M. W.; Hotfiel, Thilo; Grim, C. (Journal of Experimental Orthopaedics, 2019)
Background: It is frequently observed that overloading the foot can impair bone and soft tissue healing and can lead to harmful sequelae (i.e. ulcers, stress reactions) in context of pre-existing tissue disabilities. In terms of offloading, hindfoot relief devices are commonly applied as a non-operative treatment as well as after various surgical procedures for hindfoot disorders. Despite their common use, there is a paucity of data comparing different orthotic devices with respect to changes in plantar pressure distributions. The aim of this study was to investigate plantar loadings in hindfoot relief devices of different designs. Methods: Twenty-five healthy participants (13 women, 12 men; (mean ± SD) age 37 ± 14 years; BMI 23 ± 4 kg/m2) were recruited. Plantar pressure distributions were collected using i.) a neutral shoe, ii.) a hindfoot relief shoe (HRS) and iii.) a hindfoot relief orthosis (HRO). Peak pressure values were measured via dynamic pedobarography during walking and were analysed from four different plantar regions: the hindfoot, midfoot, metatarsal I-V and forefoot. As a reference standard, the normal walk using neutral shoes served as the condition for full weight-bearing. Results: Concerning the hindfoot, using the HRS as well as the HRO resulted in significant decreases in plantar pressures compared to baseline values that were obtained with the neutral shoe (− 52% for the HRS and − 52% for the HRO, p < 0.001). Significant increases in peak pressures were found in the midfoot region for both devices (HRS: 32%, p = 0.002; HRO: 47%, p < 0.001). For the metatarsal region, peak pressures were found to decrease significantly (HRS: − 52%, p < 0.001; HRO: -17%, p = 0.034). With respect to the forefoot, a significant reduction in peak pressures using the HRS (− 41%, p < 0.001) was detected, whereas the HRO did not lead to significant changes (− 4%, p = 0.691). Conclusions: Both the HRO and HRS significantly reduced plantar hindfoot pressure, corresponding to a relative decrease of nearly 50% of the baseline. Nevertheless, the adjacent midfoot zone displayed a significant increase in plantar pressure values for both devices. Supported by these findings, physicians should cautiously consider a substantial increase in midfoot loading, especially in patients affected by additional midfoot injuries or accompanying impairments of tissue healing. Level of evidence: IV, Case series.
CRIS-Team Scopus Importer:2019-10-11
Keywords: Biomechanics; Foot; Hindfoot relief shoes; Kinetics; Pedobarography; Plantar pressure; Plantar ulcers; Stress fractures